Agglomérations, vici et castra du Nord de la Gaule (iiie-vie s. apr. J.-C.) : esquisse d’un bilan - Michel Kasprzyk; Martial Monteil (Gallia)
This introduction sums up the main results of a series of analyses which describe a state of the urban frame evolution of a part of Northern Gaul and Germania during the Late Antiquity. Based on regional approaches and case studies, this issue allows to measure the varied rhythms of the towns – mainly small towns – evolution, and to examine the changes, which occur in the fields of public equipments, shapes of housing or economic activities. These papers allow us to conclude that a partly renewed urban network is emerging, from the 5th c. AD, after a transformation which mostly occurred in the 3rd-4th c. AD.